Toward an Expansive Phenomenology of Religious Existence - Simmons, J. Aaron (Sophia, 2014)
This review of Kevin Schilbrack’s—Philosophy and the study of religions: a manifesto—is part of a review symposium featuring reviews by Andrew Irvine, J. Aaron Simmons, and James McLaughlin and a reply by Kevin Schilbrack.